geopolitical and economic implications The Belt and Road Initiative on the future of Iraq: (Study in geopolitics) - Hamadi, Adnan Abdullah (Al-Adab Journal, 2022)
Through the Belt and Road Initiative, China confirms its rise as an international power to compete with the United States of America, and thus aims to follow a policy of cordoning off American attempts and responding to its strategy based on heading towards Asia (Pivot to Asia) and preventing its naval fleets from controlling the waterways of the world, which threatens to close China's energy and trade corridors in the event of military tensions, and China, on the other hand, emphasizes the strengthening of China's soft power. As for the internal causes, through the project, China seeks to support the interior and western regions of China, which suffer from slow economic growth, through the transfer of goods and services from the eastern ports, in which capital and labor are concentrated, which helped raise their economic growth rates.